RESEARCH ON THE RESIDUAL STRESS OF THE CRYSTAL SURFACE DURING LAPPING PROCESS BASED ON A SINGLE PARTICLE MODEL - WANG XiaoBo; XIE RuiQing (Jixie qiangdu)
In order to understand the formation mechanism of the residual stress of the lapping surface of laser crystal,a single particle model of a YAG crystal workpiece during lapping process was established by the finite element analysis software ANSYS. The material plastic properties of YAG crystal were studied,and the influence of mechanical action of abrasive particles on the distribution of residual stress of crystal surface was analyzed. The result shows that the residual stress of the lapping surface of YAG crystal is mainly compressive stress（ the maximum distribution depth is ≈ 3 μm） when the single particle load on the workpiece surface is 18 m N. However,there is tensile stress in the shallow surface layer（ depth < 150 nm）,and the maximum tensile stress exceeds the ultimate tensile strength of the material. The excessive tensile stress will induce microcracks on the crystal surface. When the single particle load is reduced to 2. 3 m N,the maximum residual tensile stress of the crystal surface is less than the ultimate tensile strength of the material,which can achieve the plastic processing of YAG crystal.